(untitled) (Philological Studies, 2020)
This text sheds light on the meaning of the popular phrases "unbearable lightness of being" and "feeling of austerity" in Milan Kundera’s novel "The Book of Laughter and Oblivion" and Philip Kaufman’s film "Unbearable Lightness of Being", which is based on Kundera’s novel of the same name. This explanation is rooted in his subversive magically realistic poetics, which are related to his emigrant life path and the inability to directly write about the burning topics of freedom, terror, morality, human relations, promiscuity, love. Special emphasis is put on the poetics of magical realism, which is explained as the way in which Kundera expresses his artistic ideas. Specifically, many magically realistic elements are present in the above-mentioned works, such as: verbal magic; magical atmosphere; merging the real and the magical; displacement of time, space, identity. The representation of all these magically realistic elements is interpreted as a shield that covers a new objectification of the reality of East and West and of the postmodern world in general, which is characterized, as Kundera sarcastically states, by the phrase "unbearable lightness of being".